REKONSILIASI KAS UMUM DAERAH KABUPATEN TANAH LAUT - Rina pebriana; Eni Suasri (Jurnal Riset Akuntansi Politala, 2022)
Bank Reconciliation is a procedure used by a company in terms of financial records. Companies and government agencies in recording financial statements carry out bank reconciliation. Bank reconciliation aims to prevent and minimize the occurrence of fictitious transactions, both those carried out by the bank and by the regional General Treasury. In addition, to ensure that the company's cash has been deposited into the bank and to find out the number of expenses or receipts recorded by the bank, but have not been recorded in the Regional General Treasury. This study used a method of comparing cash balances in regional general cash with bank statements by making bank records as a reference. Based on the results of the reconciliation that has been carried out, there is a difference in cash receipts and expenditures of IDR 27,045,944,080.